Ocular graft-versus-host disease after allogeneic hematopoietic stem cell transplantation in a pediatric population - Cinthia Kim; Patricia Cabral Zacharias Serapicos; Cintia Monteiro Lustosa; Adriane da Silva Santos Ibanez; Victor Gottardello Zecchin; Lauro Augusto de Oliveira (Hematology, Transfusion and Cell Therapy)
Aim: To determine the prevalence of ocular graft-versus-host disease after allogeneic hematopoietic stem cell transplantation and to characterize the risk factors associated with its development in a pediatric population. Methods: This retrospective chart review included 105 patients during a five-year period (2013–2017) from the Pediatric Oncology Institute (GRAACC-UNIFESP). The diagnosis of graft-versus-host disease was performed by the treating hematologist in conjunction with an ophthalmologist in accordance to National Institutes of Health (NIH) consensus criteria. Results: Systemic graft-versus-host disease occurred in 44 of 105 (41.9%) patients, predominantly in males (54.5%) whereas ocular disease was diagnosed in seven (6.7%) of the patients. All the analyzed risk factors including diagnosis, type of conditioning regimen, use of radiotherapy in conditioning, donor sex, type and source of graft, human leukocyte antigen mismatch, and sex mismatch were not statistically significantly associated with the development of ocular disease, except for age. Ocular graft-versus-host disease patients presented a higher mean age compared to patients without ocular disease (p-value = 0.015). Conclusion: Although less prevalent than in adults, ocular morbidity remains a concern in pediatric patients following allogeneic transplantation. Early diagnosis and regular ophthalmic follow-ups are recommended after the transplantation regardless of systemic graft-versus-host disease status.